Treatment of Diabetes and Long-Term Survival After Insulin and Glucokinase Gene Therapy - Callejas, David (American Diabetes Association, 2013)
Diabetes is associated with severe secondary complications, largely caused by poor glycemic control. Treatment with exogenous insulin fails to prevent these complications completely, leading to significant morbidity and mortality. We previously demonstrated that it is possible to generate a “glucose sensor” in skeletal muscle through coexpression of glucokinase and insulin, increasing glucose uptake and correcting hyperglycemia in diabetic mice. Here, we demonstrate long-term efficacy of this approach in a large animal model of diabetes. A one-time intramuscular administration of adeno-associated viral vectors of serotype 1 encoding for glucokinase and insulin in diabetic dogs resulted in normalization of fasting glycemia, accelerated disposal of glucose after oral challenge, and no episodes of hypoglycemia during exercise for >4 years after gene transfer. This was associated with recovery of body weight, reduced glycosylated plasma proteins levels, and long-term survival without secondary complications. Conversely, exogenous insulin or gene transfer for insulin or glucokinase alone failed to achieve complete correction of diabetes, indicating that the synergistic action of insulin and glucokinase is needed for full therapeutic effect. This study provides the first proof-of-concept in a large animal model for a gene transfer approach to treat diabetes.